Characterization of the various functional pathways elicited by synthetic agonists or antagonists at the melatonin MT1 and MT2 receptors. Issue 1 (29th December 2019) - Legros, Céline; Dupré, Clémence; Brasseur, Chantal; Bonnaud, Anne; Bruno, Olivier; Valour, Damien; Shabajee, Preety; Giganti, Adeline; Nosjean, Olivier; Kenakin, Terrence P.; Boutin, Jean A.
Abstract: Melatonin is a neurohormone that translates the circadian rhythm to the peripheral organs through a series of binding sites identified as G protein‐coupled receptors MT1 and MT2 . Due to minute amounts of receptor proteins in target organs, the main tool of studies of the melatoninergic system is recombinant expression of the receptors in cellular hosts. Although a number of studies exist on these receptors, studies of several signaling pathways using a large number of melatoninergic compounds are rather limited. We chose to fill this gap to better describe a panel of compounds that have been only partially characterized in terms of functionality. First, we characterized HEK cells expressing MT1 or MT2, and several signaling routes with melatonin itself to validate the approach: GTPγS, cAMP production, internalization, β‐arrestin recruitment, and cell morphology changes (CellKey ® ). Second, we chose 21 compounds from our large melatoninergic chemical library and characterized them using this panel of signaling pathways. Notably, antagonists were infrequent, and their functionality depended largely on the pathway studied. This will permit redefining the availability of molecular tools that can be used to better understand the in situ activity and roles of these receptors.